Felt Accountability and Managerial Performance: The Moderation Effects of Organizational Commitment and Work Motivation (Empirical Study on Medical Managers of Community Health Centers in Pemalang Regency) - Munasifa Naelal; Pratolo Suryo (SHS Web of Conferences)
This research aims to scrutinize the effect of felt accountability on managerial performance with organizational commitment and work motivation as moderating variables. This test employed managerial performance as the dependent variable, organizational commitment and work motivation as moderating variables, and felt accountability as the independent variable. The samples used were from the medical managers of community health centers in Pemalang Regency. While the type of data used in this research was primary data, the sampling method utilized was purposive sampling. After performing the questionnaire distribution process, a sample of 53 respondents was obtained. Hypothesis testing in this study was conducted using Structural Equation Modeling (SEM) analysis based on Partial Least Squares (PLS) utilizing the SmartPLS application version 4.0.9.5. The research findings revealed that felt accountability exerted a positive and significant effect on managerial performance. Organizational commitment strengthened the influence of felt accountability on managerial performance. In comparison, work motivation did not moderate the effect of felt accountability on managerial performance.